Archaeal contribution to carbon-functional composition and abundance in China’s coastal wetlands: Not to be underestimated - Yang, Meiling; Liu, Na; Wang, Baoli; Li, Yajun; Li, Jianfeng; Liu, Cong-Qiang (Frontiers in Microbiology, 2022)
Microbial diversity together with carbon function play a key role in driving wetland carbon cycle; however, carbon functional genes as more direct indicators of carbon cycle, their predominant microbes and biogeographic patterns have not been well known in coastal wetland. Therefore, microbes and carbon functional genes and related environmental factors were investigated in twenty-one wetlands along China΄s coast to understand the above concerns. The results indicated that carbon functional gene composition was mainly determined by archaea community rather than bacteria, and Nanoarchaeaeota contributed the most of abundance. Compared with microbes, carbon functional composition was more stable because of the highest Shannon diversity and archaea functional redundancy. Deterministic and stochastic processes respectively dominated microbial and carbon functional community assembly, DGT-Fe governed archaea and carbon functional community by coupling with nitrogen and carbon biogeochemical cycles, while bacterial communities with different abundance were affected by DGT-NH4-N and SOC/SON. This study highlighted predominated role of archaea in carbon functional gene and stability of carbon functional composition, and thus provides a new insight into understanding the dominant microbial-driven carbon cycle and the evaluation of carbon function in coastal wetland.